Compilation and analysis of international from-whom-to-whom financial stock table for Japan, Korea, the United States, and China - Satoru Hagino (SpringerOpen, 2021)
Abstract This paper discusses the development of international flow of funds accounts; it compiles and analyzes such accounts with a focus on the global financial crisis. For this purpose, we compile from-whom-to-whom financial stock tables for Japan, Korea, the United States, and China and combine these tables to generate a four-country international from-whom-to-whom financial stock table. Input–output analyses reveal that nonfinancial corporations in the four countries have the largest liability power-of-dispersion and that the Japanese government’s liability power-of-dispersion is large. In contrast, the financial institution sector in Japan has the largest asset power-of-dispersion. In the future, the table could be expanded to include other major Asia–Pacific countries and linked to Euro-area from-whom-to-whom financial stock tables to provide a global from-whom-to-whom financial stock table.